PENGARUH REPUTASI UNDERWRITER, UKURAN PERUSAHAAN, PROFITABILITAS PERUSAHAAN, DAN FINANCIAL LEVERAGE TERHADAP TINGKAT UNDERPRICING SAHAM PADA PERUSAHAAN YANG GO PUBLIC DI BURSA EFEK INDONESIA PERIODE 2011-2014 - RIZKA RAMADHANI; ISKANDAR -; DHINA MUSTIKA (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2016)
This research aim to analyze of Underwriter Reputation, Firm Size, Profitability, and Financial Leverage on Underpricing by using an approach multiple linear regression model. Sampling method that used is proposive sampling and the result are 79 companies as sample.The data used are secondary data, namely the financial statements and prospectus statements of companies listed on the Indonesia Stock Exchange in 2011-2014. Simultaneous testing concluded that all the independent variables affect the dependent variable at 14 percent. Partial  testing  indicates that underwriter reputation have an significant influence on underpricing. The firm size, profitability, and financial leverage do not have significant influence to underpricing.Keywords: Underpricing, underwriter reputation, firm size, profitability, and  financial leverage.